Размышления о субстанциальном единстве материального и идеального - Ивакин, Алексей Аркадьевич; Івакін, Олексій Аркадійович; Ivakin, Aleksej (My University, 2009)
Author aims to prove, that the material and ideal can not be considered as anything derivative, because always and in any form of beings they are its inalienable properties, and their dialectical contradictory correlation serves as a source of development of all existence.
Ивакин А. А. Размышления о субстанциальном единстве материального и идеального / А. А. Ивакин // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 26-34.
Keywords: Бог; природа; материальное; идеальное; отображение; диалектика; субстанция; развитие; матеріальне; ідеальне; відображення; діалектика; субстанція; розвиток; God; nature; material; ideal; reflection; dialectics; substance; development